(Be)Coming Home : figurations of exile and return as poetics of identity in contemporary Anglo-Caribbean literature - Ravizza, Eleonora; Justus Liebig University Giessen (My University, 2012)
The object of this work are the dialectic intersections and reciprocal transformations of the themes of exile , home and return in a literature issued from the cultural shipwreck, multiple diasporas, and violent, colonial encounters which shaped the Caribbean. The theoretical framework of the book can be summarized in three main hypothesis.1. That a return is a highly mediated act. Coming home is, in other words, never a direct act; it implies traversing the space of the other, the space where the self is conversely perceived as other. Home comes into being through the mediation of the other.2. That the voyage home in Caribbean literature is actually a voyage-in sensu Said, a journey of hybridization undertaken by Third World intellectuals towards what may considered as the centers of literature and culture. Return is indeed a highly self-reflexive motif. It is a journey whose geography is, above all, that of the literary text, of language, and of the multiple connections that link the literary artifact to a multiplicity of intertexts or to use a deleuzian terminology, to multiple, interconnected machines of sense and representation. 3. That the journey home is a journey of subjectivation (sensu Althusser); that the subject of a return does not pre-exist the return but comes into being precisely through the journey. Caribbean literary homecomings enact and perform the process through which subjects are interpellated by language (my main reference having been, in this sense, Jean-Jacques Lecercle´s Marxist philosophy of language), and through which they may, conversely, counter-interpellate language. This process of counter-interpellation has been addressed in terms of Deleuze and Guattari´s concept of minor literature, allowing for a significant parallel between the idea of (be)coming home and that of becoming-minor . The idea that never-ending literary journeys of homecoming construct multiple, discrepant visions of home has been paralleled by the idea that the process of reading a text is also a never-ending process a process through which a text is called into play. Following the thread traced by these three, interconnected theses the work of four different Caribbean writers was addressed: V. S. Naipaul, David Dabydeen, Marlene NourbeSe Philip, and Derek Walcott. All textual analysis put a special emphasis on the relationship between author and language. Caribbean literature emerges thus as a site of translation and untranslatability. As the theoretical premise of this study has been the idea that language is a site of subjectivation through interpellation, the concept of translation has gone much beyond the linguistic and cultural sphere, also embracing the sphere of personal identity. The word untranslatability refers to the friction and impossibility of conciliation between self and other. Traversing the space of the other in order to come home has been discussed not as an irenic process, but rather as a form of conflict. It has therefore been suggested that literature should be considered as a form of what de Certeau called heterology , a science of the other , whereas the word science must be used within inverted commas, as Jean-Jacques Lecercle highlighted in his article on Kafka, Minority, Marxism (2003). More specifically, the other is always-already located in language; literature allows us to explore the fragile and unstable boundaries between identity and alterity, to alternate movements of expatriation and repatriation, to deterritorialize and reterritorialize the terrain of selfhood and otherness.
Figurationen von Exil und Rückkehr in der englischsprachigen karibischen Gegenwartsliteratur
Keywords: ddc:820